Relative Afferent Pupillary Defect with Normal Vision: Unique Localisation to the Contralateral Brachium of the Superior Colliculus. (3rd March 2020) - Donaldson, Laura; Rebello, Ryan; Rodriguez, Amadeo R.
ABSTRACT: A relative afferent pupillary defect (RAPD) is a very important clinical finding in neuro-ophthalmology, and is almost always accompanied by other signs of afferent visual pathway dysfunction including visual field defect, decreased acuity and abnormal colour vision. We present a case of isolated RAPD and describe the anatomic localisation of the lesion with a review of the literature for similar cases.